Producer Company to Facilitate Livelihood Solutions Case Study of Cotton Seed Producers in Rajasthan - Mathur, I. J.; Intodia, S. K.; Agarwal, S. K. (Indian Farming, 2015)
Under the NAIP, the Dungaria Agro Producer Company, took great strides becoming a self-sustaining organization capable of empowering small and marginal farmers. With use of self-help principles they could create 45 Farmer Business Groups of 666 members which facilitated savings, generated marketing power and allowed for training and capacity building in the villages.